Upcycling Waste Water Sludge for Preparing Clay pellets as Plant Grow Material - Noisuwan, Phichamon; Poonjarernsilp, Chantamanee; Srisuk, Tanyalak; Maneesuphachoke, Phatcharaporn; Suksiri, Pakaporn (Journal of Advanced Development in Engineering and Science, 2026)
This research was upcycling waste sludge for preparing the growing media expanded clay from wastewater sludge including zinc sulfide together with clay. The effect of the ratio of wastewater sludge to clay was studied at 50:50, 40:60, 30:70 and 0:100% wt. and the effect of the calcined temperature at 700, 800, 900 ºC for 30 minutes on the density and percentage of water adsorption of the prepared growing material were studied. The experimental results showed that every ratio of wastewater sludge to clay had a higher percentage of water adsorption than clay pellets form clay. This was because of zinc sulfide waste water sludge have high porosity, which can be observed from scanning electron microscopy (SEM) images. The effect of calcined temperature showed that the temperature did not affect the density of the clay pellets. Moreover, it was also found that zinc sulfide still contained in the expanded clay after calcination from the EDX result. The results of the experiment were concluded that the optimized condition prepared expanded clay pellets with waste water sludge was 50:50 %wt. ratio of waste water sludge to clay at 800°C of calcination temperature. By this optimal condition, the expanded clay pellets had density of 1.97 g/cm3, water adsorption of 17.5%, pH 5.7 and 412ppm zinc content from zincon assay from leaching test. The estimation cost of expanded clay pellets with waste water sludge at the optimal condition was also calculated, resulting 23 bath/kilograms.